Deep Learning Based Security Schemes for IoT Applications: A Review - Othman, Mina; askar, shavan; Ali, Daban; Ibrahim, Media Ali; Abdullah, Nihad (AI Society & STMIK Indonesia, 2024)
Due to its widespread perception as a crucial element of the Internet of the future, the Internet of Things (IoT) has garnered a lot of attention in recent years. The Internet of Things (IoT) is made up of billions of sentients, communicative